Comparative Study of Voxel-Based Epileptic Foci Localization Accuracy between Statistical Parametric Mapping and Three-dimensional Stereotactic Surface Projection - Wang, Kailiang; Liu, Tinghong; Zhao, Xiaobin; Xia, XiaoTong; Zhang, Kai; Qiao, Hui; Zhang, Jianguo; Meng, Fangang (Frontiers in Neurology, 2016)
Introduction: 18F-FDG-PET is widely used to help localize the hypometabolic epileptogenic focus for presurgical evaluation of drug-refractory epilepsy patients. Two voxel-based brain mapping methods to interpret 18F-FDG-PET, statistical parametric mapping (SPM), and three-dimensional stereotactic surface projection (3D-SSP), improve the detection rate of seizure foci. This study aimed to compare the consistency of epileptic focus detection between SPM and 3D-SSP for 18F-FDG-PET brain mapping analysis. Methods: We retrospectively reviewed the clinical, electroecephalographic, and brain imaging results of 35 patients with refractory epilepsy. 18F-FDG-PET studies were revaluated by SPM, 3D-SSP, and visual assessment, and the results were compared to the MRI lesion location and to the presumed epileptogenic zone (PEZ) defined by video-EEG and other clinical data. A second consistency study compared PET analyses to histopathology and surgical outcomes in the 19 patients who underwent lesion resection surgery. Results: Of the 35 patients, consistency with the PEZ was 29/35 for SPM, 25/35 for 3D-SSP, 14/35 for visual assessment, and 10/35 for MRI. Concordance rates with the PEZ were significantly higher for SPM and 3D-SSP than for MRI (P<0.05) and visual assessment (P<0.05). Differences between SPM and 3D-SSP and between visual assessment and MRI were not significant. In the 19 surgical patients, concordance with histopathology/clinical outcome was 14/19 for SPM, 15/19 for 3D-SSP, 14/19 for visual assessment, and 9/19 for MRI (P>0.05). A favorable Engel outcome (class I/II) was found in 16 of 19 cases (84%), and failure of seizure control was found in 3 of 19 patients (class III/IV). Conclusion: Voxel-based 18F-FDG-PET brain mapping analysis using SPM or 3D-SSP can improve the detection rate of the epileptic focus compared to visual assessment and MRI. Consistency with PEZ was similar between SPM and 3D-SSP; According to their own characteristics, 3D-SSP is recommended for primary evaluation due to greater efficiency and operability of the software, while SPM is recommended for high-accuracy localization of complex lesions. Therefore, joint application of both software packages may be the best solution for FDG-PET analysis of epileptic focus localization. Keywords: Epilepsy; Statistical Parametric Mapping; 18F-FDG-PET; 3D-SSP; Epileptic focus